Physical Vapour Deposition on corrosion resistance: A review - A., Shah; S., Izman; Siti Nurul Fasehah, Ismail; Mas Ayu, Hassan; R., Daud; Mohammed Rafiq, Abdul Kadir (Asian Research Publishing Network (ARPN), 2018)
Physical Vapour Deposition (PVD) is one of the versatile surface modification method commonly used in the manufacturing of coatings, powders, fibres, and monolithic components. The applications of PVD are cutting tools, decorative, aerospace industries and biomedical application. The main advantages of PVD coating as compared with other surface modification methods is low processing temperature thus can be used on variety of materials. However PVD coating has limitation due to low corrosion resistance especially when it contact with Cl ion in sea water and body fluids. Hence, this review explains the overview of PVD coating on corrosion resistance in body fluids and sea water. The types of PVD coating and parameter commonly used as well as issue related to PVD coating is discussed in this paper.